MODERN TECHNIQUES FOR FACE AND NECK PHLEGMONS TREATMENT - O. A. Paramonova; Ju. P. Savchenko; T. V. Gerbova; A. G. Uvarova (Кубанский научный медицинский вестник, 2018)
Aim. In the course of this study we carried out the analysis of clinical course features and assessment of microbiological structure of the wound surface in patients with face and neck phlegmons. The etiologic cause of the disease may be hemolytic streptococcus, different types of staphylococcus, mixed flora and anaerobic bacteria.Materials and methods. All patients required urgent surgical intervention: wide opening, drainage of cellular spaces with the subsequent irrigation with antiseptic solutions with the application of a combination of wound coverings "Aquacel Ag + Hydrofiber dressing", "Aquacel Ag Foam Hydrofiber dressing" and "Granuflex" (ConvaTec, the USA) with proper antibacterial therapy.Results. Comparison of clinical observations (favorable course of inflammatory process) and obtained microbiological assessment (quicker decrease of microbial content in the wound) confirms validity, high efficiency of wound covering application and clear advantage in comparison with traditional gauze bandages.Conclusion. The analysis of the causes of phlegmon on the face and neck over the past 5 years has shown a significant increase in the number of patients with traumatic, tonsilogenous and odontogenic phlegmons of the face and neck. The modern high-efficient method of local treatment with the use of wound coverings combinations makes it possible to suppress the purulent-inflammatory process at the early stage, to put the secondary stitches and shorten the period of treatment of patients.